The Influence of Work Motivation and Competence on Employee Performance In The Directorate of Fleet and Engineering PT. Pelni (Persero) With Career Development As an Intervening Variable - Apriyani, Naumi; Dirganthara, Emanuel Bayu (Journal Research of Social Science, Economics, and Management, 2023)
This study aims to explain how the influence of motivation and work competence on employee performance with career development as an intervening variable. This study used 105 employees of the Directorate of Fleet and Engineering PT. PELNI (Persero) as a sample. Collecting data using interviews, observation and questionnaires. This study uses Structural Equation Modeling (SEM) data analysis with instrument testing using the Partial Least Square (PLS) method. The results of this study indicate that (1) Motivation has a positive and significant effect on career development, (2) Work competence has a positive and significant effect on career development (3) Motivation has a positive and significant effect on performance (4) Work competence has a positive and significant effect on performance (5) Career development has a positive and significant effect on performance (6) Motivation has a positive and significant effect on performance through career development as an intervening variable and (7) Work competence has a positive and significant effect on employee performance with career development as an intervening variable.